The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1590/s0102-86502013001000002
|View full text |Cite
|
Sign up to set email alerts
|

Experimental model for the study of soft tissue fixation methods on skin-pericranium flaps in rats

Abstract: PURPOSE:To develop an experimental model to study and radiologically monitor displacement of skin flaps in the pericranium of rats subjected to traction and surgical fixation using suture anchored in a skull bone tunnel or with N-butyl-2-cyanoacrylate (Histoacryl TM ) surgical adhesive. METHODS:Radiological markers were placed in the subcutis of Wistar rats undergoing subperiosteal detachment of the pericranium with pulling and fixation of the flap. We performed radiography on postoperative days 3, 7, 14, 21, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In our study, we emphasized the importance of developing an experimental model for the study of soft tissue fixation methods and their tissue reactions. We found that the adhesive n-butyl-2-cyanoacrylate is more reactive than suture anchored in a skull bone tunnel; thus, adhesive promotes increased migration of PMN cells and fibroblasts corresponding to the higher repositioning of the flaps in the long term 18 . We also observed during the collection of specimens for histological analysis the presence of cover slip adhesive polymerized between the soft tissue and the bone plate.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…In our study, we emphasized the importance of developing an experimental model for the study of soft tissue fixation methods and their tissue reactions. We found that the adhesive n-butyl-2-cyanoacrylate is more reactive than suture anchored in a skull bone tunnel; thus, adhesive promotes increased migration of PMN cells and fibroblasts corresponding to the higher repositioning of the flaps in the long term 18 . We also observed during the collection of specimens for histological analysis the presence of cover slip adhesive polymerized between the soft tissue and the bone plate.…”
Section: Discussionmentioning
confidence: 83%
“…This was shown in the treated groups, in which the deposition of type I collagen was higher than that in the control group on postoperative day 7. Although the degree of collagen deposition was similar among the three groups at the end of the experiment, when the flap displacement was analyzed with a radiological control, we found the need to use soft tissue fixation methods to maintain the proposed tissue repositioning 18 .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation